NEITHER BY FORCE, NOR BY REASON. THE FAILED ATTEMPT OF CHILE ’S NATIONAL STATE TO INCORPORATE THE MAPUCHE AND PEHUENCHE PEOPLES. (1810-1835) - Peralta Cabello, Paulina (Revista de Historia Social y de las Mentalidades, 2025)
This article analyzes the relations between Chile’s recently established republican State and the indigenous communities then living south of the Bío Bío River. More specifically, it identifies, since the beginnings of the independence process, but especially after the 1820’s, a will to incorporate into the national project the territories situated south of this frontier, as well as their inhabitants. Among the legal and political strategies displayed by the ruling groups to materialize this purpose, one can identify an early offer of Chilean nationality, as well as a particular form of citizenship defined by duties rather than political rights. However, this strategy could not be implemented because of the stubborn resistance put up by most indigenous communities with respect to the new republican regime, whose alleged benefits for themselves they failed to grasp. It is likewise sustained that the natives’ resistance not only resulted in the failure of that strategy, but also undermined the “enlightened” and inclusive discourse characteristic of the early decades, forcing its replacement, starting in the mid-1830’s, by a more exclusionary one, more interested in territorial wealth than in the indigenous inhabitants.